Post-anodic formation of luminescent porous silicon layers in atmospheric environment - Makara, V.A.; Vakulenko, O.V.; Shevchenko, V.B.; Dacenko, O.I. (Functional Materials, 2005)
The changes occuring in HF pre-etched porous silicon (PS) samples during aging are studied by measurement of photoluminescence (PL) and IR transmission spectra. The PL behavior of the etched sample is found to depend on the time of PS pre-exposure to the air after anodizing and, hence, on the initial luminescence quantum yield. The results are explained by the PS structure modification during the etching and oxidation of the samples.